The Effectiveness of the Utilization and Distribution of Productive and Consumptive Zakat in the 5 Programs of BAZNAS Batam City (A Case Study of BAZNAS Batam City) - Muhammad Fazmi; Yayat Sujatna (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research investigates the effectiveness of the utilization and distribution of zakat across five key programs of BAZNAS Batam City: Batam Makmur, Batam Cerdas, Batam Sehat, Batam Taqwa, and Batam Peduli. The study employs several analytical tools, including the Allocation to Collection Ratio (ACR), Fishbone Diagram, and the CIBEST Model. Findings reveal that the Batam Makmur program has the lowest distribution rate at 7% when compared to the other programs. Based on ACR analysis, BAZNAS Batam City falls within the effective category, although the distribution of productive zakat remains suboptimal. The Fishbone Diagram highlights critical challenges, particularly related to human resources and the educational level of mustahik. Furthermore, the CIBEST Model indicates that zakat distribution contributes positively to the material and spiritual well-being of mustahik. The study suggests enhancing mustahik education and adopting digital zakat distribution systems as key strategic improvements.